An evaluation of project management processes in public sector organizations like Public Works Department (PWD) - Mouri, Hafsa Rahman (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.